Prevalence of Anxiety and Depression and Their Association with Health-Related Quality of Life Among Oncology Patients in Iraq: A Cross-Sectional Study - Ahmed Lateef Abed Alkhaqani; Miklós Sugár; Ammar Mahmood Jaber; Ali Abbas Rahi Al-Murshedi; Dávid Sipos; Nóra Rozmann; Bence Raposa (Medicina, 2026)
Background and Objectives: Anxiety and depression are among the most common psychological symptoms in patients with cancer and are associated with morbidity and impaired health-related quality of life (HRQoL), independent of the cancer stage. This study aimed to determine the prevalence of clinically significant anxiety and depression among adult oncology patients in Iraq and quantify the independent contribution of these symptoms to HRQoL. Materials and Methods: A cross-sectional study was conducted between 1 November and 15 December 2024, at the National Oncology Hospital in Najaf, Iraq. A total of 200 adult oncology patients were enrolled using consecutive sampling. Symptoms were measured using the Hospital Anxiety and Depression Scale (HADS), and HRQoL was measured using the Functional Assessment of Cancer Therapy-General (FACT-G). Descriptive statistics were used to summarize sample characteristics. Group comparisons were performed using Pearson’s chi-square test, the Fisher–Freeman–Halton exact test with Monte Carlo estimation, and one-way ANOVA, as appropriate. Associations among continuous variables were assessed using Pearson’s correlation and multiple linear regression. Statistical significance was set at p < 0.05. Results: The mean age (SD) was 52.2 (12.0) years, and 64.0% of the participants were male. Severe anxiety and severe depression were observed in 41.0% and 34.0% of the participants, respectively. Anxiety severity was significantly associated with age, sex, marital status, and treatment modality (all p < 0.01) and was significantly higher in females (58.3% vs. 31.2%) and unmarried patients. Depression severity was significantly associated with age (p = 0.005), sex (p < 0.001), and marital status (p < 0.001) but not with cancer stage (p = 0.223) or treatment modality (p = 0.530). The mean total FACT-G score was 58.2 (14.6), indicating low-to-moderate HRQoL. HADS-A and HADS-D were strongly intercorrelated (r = 0.741) and inversely correlated with FACT-G (r = −0.750 and r = −0.780, respectively; all p < 0.001). Multiple linear regression showed that higher HADS-A and HADS-D scores were independently associated with lower HRQoL, and the full seven-predictor model explained approximately 62% of the variance in FACT-G total scores (R2 = 0.62). Conclusions: Severe anxiety and severe depression were observed in 41.0% and 34.0% of participants, respectively. Higher anxiety and depression scores were independently associated with lower HRQoL.